Sc-doping induced cation-disorder in LiNi0.5Mn1.5O4 spinel leading to improved electrochemical performance as cathode in lithium ion batteries. (10th December 2019) - Bhuvaneswari, Subramani; Varadaraju, U.V.; Gopalan, R.; Prakash, Raju
Abstract: Ni/Mn disordered LiNi0.5 Mn1.5 O4 spinel is the most promising cathode material for lithium ion batteries due to its high energy and power densities. However, the Ni/Mn disorder coupled with high Mn 3+ content and concomitant formations of NiO/Liy Ni1-y O impurities deteriorate its electrochemical performances. To overcome this issue, Sc-doped disordered spinel LiNi0.5 Mn1.44 Sc0.06 O4 without NiO/Liy Ni1-y O impurities has been synthesized. Infrared spectroscopy, magnetic measurements and cyclic voltammetry results reveal the increase in Ni/Mn disordering of LiNi0.5 Mn1.44 Sc0.06 O4 than pristine spinel which decreases the charge transfer resistance and enhances the electrochemical performances. The XPS spectrum of LiNi0.5 Mn1.44 Sc0.06 O4 exhibits Sc2p3/2 (402.3 eV) and Sc2p1/2 (406.5 eV) bands confirming the presence of Sc 3+ in the spinel lattice. Sc-doped spinel delivers an initial discharge capacity 131 mAhg −1 with 88% columbic efficiency at 0.1C rate. Under similar condition, the undoped spinel yields only 123 mAhg −1 with 81% columbic efficiency. In addition, cycling stability of the doped spinel has increased dramatically with increase in the C-rate. At 5C, it exhibits a specific capacity of 102 mAhg −1 with 98% capacity retention even after 1000 cycles. Furthermore, it demonstrates excellent rate capability due to enhanced lithium-ion diffusion kinetics. The improved performance of the spinel can be attributed to the stabilization of the cation disordered structure. Thus, the Sc-doped spinel could be a potential cathode material for lithium ion batteries for electric vehicle applications. Graphical abstract: LiNi0.5 Mn1.44 Sc0.06 O4 spinel prepared by solution combustion shows enhanced cycling stability and rate capability than pristine LiNi0.5 Mn1.5 O4 as cathode in lithium ion batteries. Image 1 Highlights: Synthesis of phase pure Sc-doped cation-disordered LiNi0.5 Mn1.5 O4 by solution combustion method. Spherical morphology with uniform particle size. Exhibited a capacity of 102 mA h/g at 5C with capacity retention of 98% after 1000 cycles. Showed excellent rate capability (12C). The morphology of the doped spinel remains intact after prolonged cycling.